ADVANCED FABRICATION TECHNIQUE AND THERMAL PERFORMANCE PREDICTION OF U-MO/ZR-ALLOY DISPERSION FUEL PIN FOR HIGH BURNUP PWR - Suwardi Suwardi (Seminar Nasional Informatika (SEMNASIF), 2010)
In recent years, a novel class of zirconium alloys having the melting temperature of 990-1160 K has been developed. Based on novel zirconium matrix alloys, high uranium content fuel pin with U-9Mo has been developed according to capillaryimpregnation technique. The pin shows its thermal conductivityranging from 18 to 22 w/m/K that is comparably higher than UO2pellet pin. The paper presents the met-met fabrication and thermal performance analysis of the fuel in typical PWR. Thefabrication consists of mixing UO2 powder or granules and a novel Zr-alloy powder having low melting point, filling the mixture in a cladding tube that one of its end has been plugged, heating the pin to above melting temperature of Zr-alloy for an hour, natural cooling and heat treating at 300 K for ½ hr. The thermal analysis takes into account the pore and temperature distribution and high burn up effect to pellet conductivity. The thermal diffusivity ratio of novel to conventional fuel has been used as correction factor for the novel fuel conductivity. The results show a significant lowering pellet temperature along the radius until 1000 K at the hottest position. The analysis underestimates since the gap conductivity has been treated as decreased by 2 % fission gas released that is not real since the use of lower temperature, and also decreasing thermal conductivity by porosity formation will much lower. The analysis shows that the novel fuel has very good thermal properties which able to pass the barrier of 65 MWD/kg-U, the limit to day commercial fuel. The burn-up extension means less fresh fuel is needed to produce electricity, preserve natural uranium resource, easier fuel handling operational per energy produced.